Integrated Management of Cardiovascular–Renal–Hepatic–Metabolic Syndrome: Expanding Roles of SGLT2is, GLP-1RAs, and GIP/GLP-1RAs - Nikolaos Theodorakis; Maria Nikolaou (Biomedicines)
Cardiovascular–Kidney–Metabolic syndrome, introduced by the American Heart Association in 2023, represents a complex and interconnected spectrum of diseases driven by shared pathophysiological mechanisms. However, this framework notably excludes the liver—an organ fundamental to metabolic regulation. Building on this concept, Cardiovascular–Renal–Hepatic–Metabolic (CRHM) syndrome incorporates the liver’s pivotal role in this interconnected disease spectrum, particularly through its involvement via metabolic dysfunction-associated steatotic liver disease (MASLD). Despite the increasing prevalence of CRHM syndrome, unified management strategies remain insufficiently explored. This review addresses the following critical question: How can novel anti-diabetic agents, including sodium–glucose cotransporter-2 inhibitors (SGLT2is), glucagon-like peptide-1 receptor agonists (GLP-1RAs), and dual gastric inhibitory polypeptide (GIP)/GLP-1RA, offer an integrated approach to managing CRHM syndrome beyond the boundaries of traditional specialties? By synthesizing evidence from landmark clinical trials, we highlight the paradigm-shifting potential of these therapies. SGLT2is, such as dapagliflozin and empagliflozin, have emerged as cornerstone guideline-directed treatments for heart failure (HF) and chronic kidney disease (CKD), providing benefits that extend beyond glycemic control and are independent of diabetes status. GLP-1RAs, e.g., semaglutide, have transformed obesity management by enabling weight reductions exceeding 15% and improving outcomes in atherosclerotic cardiovascular disease (ASCVD), diabetic CKD, HF, and MASLD. Additionally, tirzepatide, a dual GIP/GLP-1RA, enables unprecedented weight loss (>20%), reduces diabetes risk by over 90%, and improves outcomes in HF with preserved ejection fraction (HFpEF), MASLD, and obstructive sleep apnea. By moving beyond the traditional organ-specific approach, we propose a unified framework that integrates these agents into holistic management strategies for CRHM syndrome. This paradigm shift moves away from fragmented, organ-centric management toward a more unified approach, fostering collaboration across specialties and marking progress in precision cardiometabolic medicine.